2018
DOI: 10.1044/2018_jslhr-s-17-0378
|View full text |Cite
|
Sign up to set email alerts
|

The Coexistence of Disabling Conditions in Children Who Stutter: Evidence From the National Health Interview Survey

Abstract: Purpose Stuttering is a disorder that has been associated with coexisting developmental disorders. To date, detailed descriptions of the coexistence of such conditions have not consistently emerged in the literature. Identifying and understanding these conditions can be important to the overall management of children who stutter (CWS). The objective of this study was to generate a profile of the existence of disabling developmental conditions among CWS using national data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 27 publications
2
21
0
2
Order By: Relevance
“…The prevalence of comorbid conditions, such as learning disabilities and developmental delay, is higher for CWS relative to CWNS [ 139 , 140 ]. In clinical cohorts, concomitant language, speech, and behavioral disorders (e.g., expressive language, receptive language, articulation, phonology, and ADHD) are commonly reported with stuttering [ 141 , 142 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of comorbid conditions, such as learning disabilities and developmental delay, is higher for CWS relative to CWNS [ 139 , 140 ]. In clinical cohorts, concomitant language, speech, and behavioral disorders (e.g., expressive language, receptive language, articulation, phonology, and ADHD) are commonly reported with stuttering [ 141 , 142 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, a variety of methods have been used to examine stuttering comorbidities. For example, using the National Health Interview Survey, Briley and Ellis (2018) found the presence of at least one disabling developmental condition (from among (a) intellectual disability, (b) learning disability, (c) attention-deficit/hyperactivity disorder (ADHD)/ADD, (d) seizures, (e) autism, Asperger’s, or pervasive developmental disorder (PDD), and (f) any other developmental delay) to be 5.5 times higher in children who stutter compared to children who do not. Additionally, using the 1995 Australian Health Survey, Keating, Turrell and Ozanne (2001) found children who stutter had a higher incidence of developmental delay and emotional problems as well as asthma, allergies, and deafness from among 16 pre-selected conditions.…”
Section: Introductionmentioning
confidence: 99%
“… Manning & Beck, 2013 ), inattention and hyperactivity (e.g., Donaher & Richels, 2012 ), and articulation and phonological disorders (e.g., Wolk, Conture, & Edwards, 1990 ). These studies have identified a number of disorders and conditions comorbid with developmental stuttering but were limited by 1) a reliance on either clinician or caregiver recall ( Briley & Ellis, 2018 ), 2) lack of a control population ( Blood et al, 2003 ; Donaher & Richels, 2012 ; Manning & Beck, 2013 ), and/or 3) a scope limited to preselected conditions (i.e., other potential comorbidities with stuttering may not be included on a given survey).…”
Section: Introductionmentioning
confidence: 99%
“…Interest in the study of stuttering with comorbid disorders has recently been increasing (Arndt & Healey, 2001;Blood & Seider, 1981;Briley & Ellis, 2018;Donaher, Healey, & Zobell, 2009;Donaher & Richels, 2012;Druker, Hennessey, Mazzucchelli, & Beilby, 2019;Graham, 2006;Homzie, Lindsay, Simpson, & Hasenstab, 1988;Nippold, 1990;Nippold & Schwarz,1990). In particular, in addition to articulation/phonological and/or language disorders (e.g., Arndt & Healey, 2001;Blood & Seider, 1981;Nippold, 1990), developmental disorders also have been frequently reported (e.g., Briley & Ellis, 2018;Blood, Ridenhour, Qualls, & Hammer, 2003) as comorbid disorders with stuttering. Studying the disorders that co-occur with stuttering have some advantages.…”
Section: Introductionmentioning
confidence: 99%
“…First, determining the frequencies of concomitant disorders in children who stutter (CWS) is crucial because a subgroup of children who require a di erent type of assessment, and treatment procedures than the general CWS group may emerge (Arndt & Healey, 2001). Second, the coexistence of disorders may further indicate that stuttering is not caused by a disturbance of a distinct area of the brain (Briley & Ellis, 2018). In other words, because stuttering, in some instances, may develop from disturbances along extensive neural pathways used for speech production, and overlaps with skills that are disturbed in other coexisting conditions (Smith & Weber, 2016), determining what other disorders co-occur with stuttering is essential.…”
Section: Introductionmentioning
confidence: 99%